Developing a Measure of Interpersonality - Mesa, Rica Faith Creencia; Alaron, Angel Licel Rose Adto; Cadavedo, Jamaica Manzano; Calabio, April Octa; Costa, Mark Aldrin Esguerra; Mendoza, Franceska Nicole Abinales; Panganiban, Aila Castro; Hilario, Paulito (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
This study aimed to develop a scale that measures a construct of Filipino Psychology, which is pakikipagkapwa-tao, a key construct in Filipino Psychology grounded in Enriquez’s "Kapwa" theory, which emphasizes the importance of shared identity and interconnectedness in understanding Filipino social behavior. Despite its importance, there is a lack of empirical tools to measure pakikipagkapwa-tao, creating a need for a culturally relevant and psychometrically sound instrument. With this, the study seeks to address this gap by developing a new scale that captures five dimensions of pakikipagkapwa-tao: sympathy (pakikiramay), cooperative endeavor (bayanihan), hospitality (mabuting pagtanggap sa bisita), sensitivity to others' feelings (pakikiramdam), and debt of gratitude (utang na loob). The respondents of this study were Filipino college students, aged 18 to 22 years old, currently residing in Cavite, and were enrolled in a University for Academic Year 2022- 2023. With this, the researchers of this study obtained a total number of 501 respondents.The study utilized confirmatory factor analysis (CFA) and exploratory factor analysis (EFA) as its statistical treatment. As a result, the overall scale consists of twenty-four (24) items with alphas between 0.83 and 0.67 coming from factor analysis solutions and are based on the CFA and EFA. It was shown that concepts like "convergent" and "discriminant" are true. Keywords: EFA; CFA; Test development; Convergent; Discriminant